Silvas publicas depopulatus erat (Cic. Mil. 26): "Violated" Nature, Politics and Invective in Ciceronian Rhetorical Strategy - La Bua, Giuseppe (Ciceroniana On Line, 2023)
Far removed from the modern idea of ecology, Cicero’s defence of natural habitat constitutes a powerful weapon of political struggle and invective in his forensic orations. The violation of nature, the destruction of which poses a threat to the stability of the societas, is understood – and manipulated – by the political Cicero as an attack on the res publica and, at the same time, as an act of sacrilege and hybris, punished by the divinity protecting the natural order. This contribution aims to revisit the human-nature relationship as deployed in Cicero’s rhetorical-political strategy, studying the ways in which Cicero exploits the motif of violated nature as a means of undermining the moral auctoritas of the adversary.